Exploring immuno-genetic resistance in pigs to the food-borne zoonotic pathogen, Toxoplasma gondii: A serological study in Central Italy - Torricelli, Martina; Fratto, Anna; Costarelli, Silva; Lancioni, Hovirag; Torina, Alessandra; Panzieri, Carmen; Sebastiani, Carla; Ciullo, Marcella; Cruciani, Deborah; Crotti, Silvia; Mazzone, Piera; Biagetti, Massimo (Italian Journal of Food Science, 2024)
Toxoplasmosis is a re-emerging food-borne zoonosis of warm-blooded animals caused by Toxoplasma gondii, an obligate intracellular parasite with a complex biological cycle. Until now, the genotypic approach for discovering putative resistance immuno-genetic markers has never been adopted for T. gondii infection. Thus, this study aimed, for the first time, to deepen these novel insights. In particular, pigs, reared in different farms in Central Italy, were phenotypically characterized by serological assays performed on diaphragm meat juice. Out of 179 tested animals, 98 resulted seropositive (54.74%), 57 seronegative (31.84%), and 24 doubtful (13.40%), underlining a possible re-emerging diffusion of this protozoan in the investigated areas. Contextually, an RT-PCR assay, followed by Sanger sequencing for IL-18, a pro-inflammatory cytokine with a key role upstream of the infection, was developed. At this stage, for this interleukin, significant polymorphic variations were not detected compared to the reference sequence, except in a seropositive animal. However, the starting outcomes of this novel and preliminary study will be investigated in depth with different approaches also on other target genes, with a crucial activity in the immunity pathway towards T. gondii, to unveil the possible presence of resistance genetic mechanisms and, finally, to make pork derived food safer.